What is Autohoodening? - Frost, James; Kargotis, Demetrios; Macdonald, Dash; Mortimer, Nicholas (My University, 2023)
This book section introduces Autohoodening, a practice-based research project by Post Workers Theatre that reinterprets the Kentish Hooden Horse tradition within the context of contemporary labour conditions. Drawing on historic animal guising customs, the project adapts folk performance as a critical framework to examine precarity within the gig economy. Through performance, scripting, and participatory methodologies, Autohoodening explores how traditional cultural forms can be reactivated to address present-day socio-economic realities.